2015
DOI: 10.1111/jne.12330
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Does Not Target CamkIIα Neurones to Critically Regulate the Neuroendocrine Reproductive Axis in Mice

Abstract: Insulin signalling in the brain plays an important role in the central regulation of energy homeostasis and fertility, such that mice exhibiting widespread deletion of insulin receptors (InsR) throughout the brain and peripheral nervous system display diet sensitive obesity and hypothalamic hypogonadism. However, the specific cell types mediating the central effects of insulin on fertility remain largely unidentified. To date, the targeted deletion of InsR from individual neuronal populations implicated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…Reproduction is essential for species survival. Because energy is required to locate a mate, maintain a pregnancy, and rear young, fertility is modulated by the status of energy stores [13]. Excessive energy expenditure or insufficient caloric intake in humans and rodents delays the pubertal transition and reduces fertility [4, 5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduction is essential for species survival. Because energy is required to locate a mate, maintain a pregnancy, and rear young, fertility is modulated by the status of energy stores [13]. Excessive energy expenditure or insufficient caloric intake in humans and rodents delays the pubertal transition and reduces fertility [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…A seminal paper by Brüning and colleagues [8] showed that 50% of mice lacking the IR in cells expressing nestin (NIRKO mice) displayed hypogonadotropic hypogonadism in adulthood. Targeted deletion of IRs in specific neuronal populations, however, has failed to induce the subfertile phenotype and GnRH network dysregulation of NIRKO mice [2, 3, 6, 22, 23]. For instance, Divall and colleagues found that mice with IR deletion in GnRH neurons experienced normal pubertal timing and fertility [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although insulin can act both peripherally and centrally to modulate HPG axis function, we know that insulin's central actions play a role in mediating many of its reproductive effects as mice exhibiting brain-specific deletion of insulin receptors (InsR) exhibit subfertility due to mild hypothalamic hypogonadism (Bruning et al 2000). However, in contrast to these brain-specific InsR-knockout mice, our group recently demonstrated that mice exhibiting forebrain neuron-specific deletion of InsR displayed normal HPG axis function (Evans et al 2015), which challenges the hypothesis that neuronal insulin signaling is required. Nevertheless, many findings implicate abnormal insulin signaling in the pathogenesis of reproductive dysfunction.…”
Section: Insulinmentioning
confidence: 86%